Cajal's contribution to the Histology Nervous - Encinas, Enrique (1952)
With the ceremony under the high auspices of the University is done today, Peru, pays tribute to the enlightened admiration memory of one of the most outstanding figures in the history of contemporary Spanish culture; Santiago Ramón y Cajal, wise histologist, whose work unparalleled testimony is a high human effort to the universal good, after which dominated in the fields there before you compare his work, nor more worthy of admiration for creative effort their doctrines, methods and evidence